Metachronous Bilateral Testicular Leydig-Like Tumors Leading to the Diagnosis of Congenital Adrenal Hyperplasia (Adrenogenital Syndrome) - Josip Vukina; David D. Chism; Julie L. Sharpless; Mathew C. Raynor; Matthew I. Milowsky; William K. Funkhouser (Case Reports in Pathology)
A 33-year-old male with a history of left testis Leydig cell tumor (LCT), 3-month status after left radical orchiectomy, presented with a rapidly enlarging (0.6 cm to 3.7 cm) right testicular mass. He underwent a right radical orchiectomy, sections interpreted as showing a similar Leydig cell-like oncocytic proliferation, with a differential diagnosis including metachronous bilateral LCT and metachronous bilateral testicular tumors associated with congenital adrenal hyperplasia (a.k.a. “testicular adrenal rest tumors” (TARTs) and “testicular tumors of the adrenogenital syndrome” (TTAGS)). Additional workup demonstrated a markedly elevated serum adrenocorticotropic hormone (ACTH) and elevated adrenal precursor steroid levels. He was diagnosed with congenital adrenal hyperplasia, 3β-hydroxysteroid dehydrogenase deficiency (3BHSD) type, and started on treatment. Metachronous bilateral testicular masses in adults should prompt consideration of adult presentation of CAH. Since all untreated CAH patients are expected to have elevated serum ACTH, formal exclusion of CAH prior to surgical resection of a testicular Leydig-like proliferation could be accomplished by screening for elevated serum ACTH.